Theorizing culture : an interdisciplinary critique after postmodernism - Adam, Barbara, 1945-; Allan, Stuart, 1962- (UCL Press, 1995)
An overview of cultural theory after postmodernism which provides a user- friendly introduction for students. Theorists assess the postmodernist project, mapping out the future terrain for a critical approach to cultural theory.